2007
DOI: 10.1149/1.2436612
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Development of Copper Sulfide on Copper Exposed to Humid H[sub 2]S

Abstract: Pure copper samples were exposed in an environmental chamber for 2, 4, 7, 15, and 30 days at 90% relative humidity, 40°C, and 4 ppm hydrogen sulfide ͑H 2 S͒. Samples were subsequently subjected to microscopy and microanalysis using different techniques: scanning electron microscopy, energy analysis dispersive X-ray spectroscopy, X-ray diffraction, focused ion beam ͑FIB͒, and secondary ion mass spectroscopy. The corrosion samples were cross sectioned and the different corrosion layers were imaged using FIB. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…There is general agreement that Cu 2 S (chalcocite) is formed on copper exposed to H 2 S(g) . The growth of Cu 2 S on copper exposed to moist air containing H 2 S has been observed previously and competes with formation of Cu 2 O and CuO depending on temperature and relative humidity . The results reported here indicate dominance of Cu 2 S and an absence of CuO, not surprising in the O 2 ‐purged solutions used, but the electrochemical formation mechanism could be similar and occur without the need to invoke O 2 : leftCunormalCu++normalenormalH2SnormalHS+normalH+2normalCu++normalHS+normalH2OnormalCu2S+normalH3normalO+…”
Section: Discussionsupporting
confidence: 84%
“…There is general agreement that Cu 2 S (chalcocite) is formed on copper exposed to H 2 S(g) . The growth of Cu 2 S on copper exposed to moist air containing H 2 S has been observed previously and competes with formation of Cu 2 O and CuO depending on temperature and relative humidity . The results reported here indicate dominance of Cu 2 S and an absence of CuO, not surprising in the O 2 ‐purged solutions used, but the electrochemical formation mechanism could be similar and occur without the need to invoke O 2 : leftCunormalCu++normalenormalH2SnormalHS+normalH+2normalCu++normalHS+normalH2OnormalCu2S+normalH3normalO+…”
Section: Discussionsupporting
confidence: 84%
“…During the first 7 days of exposure, the thickness of the corrosion film increased linearly, followed by a slowdown, suggesting a transition from activation control ͑where the determining step is the reaction of the corrosive species with the Cu͒ to diffusion control ͑where the diffusion of the species through the corrosive layer is more important͒. 12,13 After the slowdown behavior, an additional slower rate of linear growth ͑slower than the first week͒ was observed, possibly indicating a combination of activation and diffusion control. Figure 3 shows a typical cathodic reduction curve for one Cu coupon exposed for 2 days.…”
Section: Methodsmentioning
confidence: 99%
“…The coexistence of cuprite and chalcocite suggests that the 7 Glow discharge optical emission spectroscopy depth profiles of copper, sulphur and oxygen for copper plate exposed indoors 8 Glow discharge optical emission spectroscopy depth profiles of copper, sulphur and oxygen for copper plate exposed outdoors a low magnification image (100 times); b high magnification image (500 times); c EDX spectra for point marked in b 6 Images (SEM) and EDX spectra for copper plates exposed outdoors formation of both phases occurred simultaneously during exposure. Reid et al studied copper sulphidation at 40uC and 90%RH with 4 ppm H 2 S. 38 Depth profiling analysis of the corrosion layers by secondary ion mass spectrometry showed that chalcocite was the main component of the corrosion layer. Secondary ion mass spectrometry depth profiling showed that there was a thin cuprite layer at the interface between the corrosion layer and copper substrate.…”
Section: Amounts Of Sulphur and Chlorine In Corrosion Productsmentioning
confidence: 99%